An analysis of food security and poverty in Central Asia - Case study from Kazakhstan - Rhoe, Valerie; Babu, Suresh Chandra; Reidhead, William (Wiley, 2008)
During the transition from planned to market‐oriented economies, Central Asian countries experienced major socio‐economic shocks that increased food insecurity, malnutrition and poverty. In the last 15 years, these countries underwent economic reforms in order to transform their economies, and in response to growing food insecurity and poverty levels, they adopted food self‐sufficiency policies. For designing and implementing policy reforms, a good understanding of the magnitude of food insecurity and poverty and their determinants are required. Using the Kazakhstan Living Standard and Measurement Survey, this paper identifies a food poverty line and a total poverty line for Kazakhstan. Then poverty measures from both lines are compared and determinates of poverty are analysed. The results show that the total poverty line captures more of the poor population. Although there are some variations amongst the determinants of poverty under the two poverty lines, the strength of the common determinants is generally weaker when non‐food expenditures are included in deriving the poverty line.